1998
DOI: 10.1097/00000542-199802000-00022
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of Dexmedetomidine on Laser-Doppler Flow and Pial Arteriolar Diameter 

Abstract: These results suggest a modulation of cerebral vascular autoregulation by dexmedetomidine which may be mediated, in part, by alterations in carbon dioxide. Dexmedetomidine may have a direct action on the cerebral vessels to reduce the CBF during normo- or hypocapnia. The differences between CBFldf and pial arteriole responses to restoration of mean arterial pressure may reflect the difference in measurement techniques because laser-Doppler measurements reflect the net effect of several arterial segments on mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 33 publications
2
32
0
1
Order By: Relevance
“…However, the α 2 -adrenergic receptor agonist medetomidine, employed in the present study, is now increasingly preferred due to the ease of implementation and, more importantly still, because of its option to perform longitudinal experiments in the same animals (Pawela et al, 2008;Weber et al, 2008Weber et al, , 2006Zhao et al, 2008). Similar to α-chloralose (Lindauer et al, 1993;Nakao et al, 2001) dexmedetomidine, the active ingredient of medetomidine is known to reduce cerebral blood flow, as measured by laser Doppler flowmetry in rats (Ganjoo et al, 1998). BOLD increase in medetomidine sedated rats does not appear to differ from α-chloralose anesthetized rats, and was in the same percentage range (1-1.5%) (Pawela et al, 2008;Weber et al, 2006;Zhao et al, 2008) as observed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…However, the α 2 -adrenergic receptor agonist medetomidine, employed in the present study, is now increasingly preferred due to the ease of implementation and, more importantly still, because of its option to perform longitudinal experiments in the same animals (Pawela et al, 2008;Weber et al, 2008Weber et al, , 2006Zhao et al, 2008). Similar to α-chloralose (Lindauer et al, 1993;Nakao et al, 2001) dexmedetomidine, the active ingredient of medetomidine is known to reduce cerebral blood flow, as measured by laser Doppler flowmetry in rats (Ganjoo et al, 1998). BOLD increase in medetomidine sedated rats does not appear to differ from α-chloralose anesthetized rats, and was in the same percentage range (1-1.5%) (Pawela et al, 2008;Weber et al, 2006;Zhao et al, 2008) as observed in our study.…”
Section: Discussionmentioning
confidence: 97%
“…It seems to reduce CBF secondary to cerebrovascular vasoconstriction. 7 It does not increase ICP, demonstrates compatibility with neurophysiological monitoring, and may offer neuroprotection. 8 In this prospective randomized study, 132 patients of either sex, age between 18 and 60 years, and ASA grade I and II undergoing elective craniotomies under GA for supratentorial intracranial space-occupying lesions were included and randomly divided into two groups: Group I (dexmedetomidine) and group II (placebo).…”
Section: Discussionmentioning
confidence: 99%
“…Medetomidine can be used for long scanning sessions and has produced a consistent BOLD response in SI, SII and thalamus, similar in magnitude to those of AC experiments (Pawela et al, 2009). Nevertheless, it is known to reduce somatosensory evoked potentials (Hayton et al, 1999) and cerebral blood flow (Ganjoo et al, 1998). Medetomidine also presents physiological drawbacks as it is known to increase urination which might lead to the dehydration of the animal.…”
Section: Discussionmentioning
confidence: 99%